Implementation Contextual Teaching Learning (CTL) Model in Fiqh Lessons at MTs Darul Muta'alimin Samarinda - Rahmawati, Indriana; Julaiha, Siti; Muri'ah, Siti; Basith, Abdul; Khalidah, Khalidah (Pascasarjana Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2021)
This research is focused on implementing the contextual teaching and learning (CTL) model for Fiqh subjects at MTs Darul Muta'alimin Samarinda. The research method used is descriptive qualitative, the research subjects include the Deputy Principal for Curriculum, Fiqh subject teachers, and students. Data collection techniques were carried out using observation, interviews, and documentation, to test the validity of the data used triangulation techniques. The results showed that the implementation of the CTL model was carried out through a learning process starting from preparation by preparing a lesson plan (RPP), implementation and evaluation stages according to the components and characteristics as well as matters related to CTL learning, namely; 1) Develop students' critical thinking so that learning activities are more meaningful, 2) Provide motivation so that students can actively participate in learning activities, 3) Develop students' curiosity by providing opportunities to express opinions, 4) Utilization of media and resources learn optimally, both media based on information technology or media and resources available in the surrounding environment, 5) Implement Inquiry learning by providing opportunities to find understanding from experience, 6) Creating a learning community by forming discussion groups, 7) Reflecting and drawing conclusions from learning outcomes, and 8) Conducting an objective and authentic assessment of each student according to the student's abilities.